2017
DOI: 10.1007/s40565-017-0299-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimized and coordinated model predictive control scheme for DFIGs with DC-based converter system

Abstract: This paper proposes an optimized and coordinated model predictive control (MPC) scheme for doublyfed induction generators (DFIGs) with DC-based converter system to improve the efficiency and dynamic performance in DC grids. In this configuration, the stator and rotor of the DFIG are connected to the DC bus via voltage source converters, namely, a rotor side converter (RSC) and a stator side converter (SSC). Optimized trajectories for rotor flux and stator current are proposed to minimize Joule losses of the DF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…1, and has been widely applied in DC-interfaced wind farms [27,[29][30][31]. It consists of a rotor side converter (RSC) and a stator side converter (SSC).…”
Section: Dc-based Dfig Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…1, and has been widely applied in DC-interfaced wind farms [27,[29][30][31]. It consists of a rotor side converter (RSC) and a stator side converter (SSC).…”
Section: Dc-based Dfig Systemmentioning
confidence: 99%
“…With the increasing use of DC transmission, DC-based DFIG systems have been widely applied in a DC grid [25][26][27]. A diode-based stator converter interfaces a DFIG with a DC grid, which simplifies its converter structure, reduces its cost and improves its efficiency [26,28], however this diode-based converter has no protective ability and exposes the DFIG to DC grid faults.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An early study reported in [8] for an ac stand-alone DFIG feeding non-linear loads proposed to compensate for the harmonics by operating the grid-side converter (GSC) as an active filter. As the DFIG-dc system does not include any GSC, the only way to implement an active filter is by adding an extra converter [9], or replacing the diode-bridge with a second VSI, which turns the system into a dual-VSI DFIG [10]- [11]. Twelve-pulse rectifiers are another viable option to tackle the harmonics at the source [12].…”
Section: Introductionmentioning
confidence: 99%
“…But harmonic may reach from 5.97% to 11.66% [8]. An IGBT-based converters system consisting of a rotor side converter (RSC) and a stator side converter (SSC) connects rotor and stator with DC grid, respectively [9][10][11][12][13]. This structure has the advantages that it can reduce the current harmonic effectively and regulate the stator flux and current flexibly according to the needs of the system, not limited to AC grid.…”
Section: Introductionmentioning
confidence: 99%